Pengembangan E-Sudent Worksheets (E-SW) Berbasis Literasi Sains Dalam Pembelajaran IPA Muatan Gaya Untuk Siswa Kelas IV Sekolah Dasar - Anisa Asnawati; Sutrisno, Sutrisno; Imaningtyas, Imaningtyas (Universitas Nusantara PGRI Kediri, 2021)
This investigation means to deliver e-student worksheets based on Science Literacy with the content of force for the fourth grade students of primary school. This exploration is a type..of research and development with the ADDIE development model consisting of three.stages including..analysis,..design, and development. The assessment isinvolving material experts, media, linguists, elementary school teachers and students. The data was obtained by observations, interviews and questionnaires. Literacy-based e-student worksheets assessment is in accordance with the right aspects, the right aspects, the right aspects, and the right literacy aspects. The aftereffect of this examination indicate that the e-student worksheets according to Science Literacy is very suitable to be used for fourth grade elementary school students. This is proven based on the assessment by material experts of 96%, linguists 94%, media experts 87%, elementary school teachers get an average rating of 97%, one to one 93%, small group 86%, field test 84% if described including very good category. The implication of implementing e-student worksheet based on Science Literacy can create active, independent and meaningful learning for students, teachers can add new sources of insight, and PGSD students get an idea to conduct similar research.